"Fear, greed, and dedication": the representation of self-entrepreneurship in international English textbooks - Yuto Wahyuto; Joko Nurkamto (Journal on English as a Foreign Language, 2022)
A number of studies have reported neoliberal representation in English textbooks in a variety of contexts around the world. However, the study focusing on self-entrepreneurship as one of the critical neoliberal tenets is scantily addressed. To fill this void, the present study seeks to investigate the representation of self-entrepreneurship deliberately inculcated in English textbooks. Anchored in critical discourse analysis and Halliday